О выявлении особых свойств электромагнитных виброиспытательных стендов - Божко, А.Е.; Белых, В.И.; Мягкохлеб, К.Б. (Видавничий дім "Академперіодика" НАН України, 2008)
We have shown that polyharmonic vibrations are well reproduced by a vibrobench with one movable platform and several magnetic circuits. A method of compensation of the diminution of an air clearance is proposed.